RUTE AMAN SELAMAT SEKOLAH (RASS) DI KOTA SALATIGA - Purwoko Purwoko; Budi Dwi Hartanto; Arbie Sianipar (Jurnal Penelitian Transportasi Darat, 2016)
ABSTRACTSchool routes safety is part of the management and traffic engineering including the provision of public transportation with traffic control and the use of the road network on the school zone. The purpose of this study is to analyze the safety routes for students including the supporting facilities such as the public transportation route, road pedestrian, cyclist lanes, School Safety Zone. The analytical used in this study are the Capacity Manual methods for Indonesian Highway, Cross Tab Analysis, Pedestrian Analysis and Descriptive Analysis. The results of the study showed that the density of the streets for 5 observation zone are about 0.13 to 0,69 with the level of service at the interval A and F, nevertheless the number of pedestrians larger than traffic volume with high-speed. For this, facilities for School Safety Zone needs to be developed. The result of Cross Tab analysis is motorcycle most widely used as transportation mode which followed by public transport users and pedestrians. Therefore it is necessary to provide facilities for pedestrians/sidewalks and public transit stations to protect all road users. The result of pedestrian survey showed some roads required pelicans wait and zebra crossing because of the high volume of traffic and the number of pedestrians crossing. The result of interviews with students showed that the percentage of students who use public transport is about 19.57%, 60.15% motorcyclists, 7.97% pedestrians and cyclists, public buses, private cars 12.31%.ABSTRAKRute Aman Selamat Sekolah merupakan bagian dari kegiatan manajemen dan rekayasa lalu lintas berupa penggunaan jaringan jalan, pengendalian lalu lintas dan penyediaan sarana angkutan umum dari lokasi pemukiman menuju sekolah. Tujuan dilakukannya penelitian ini adalah menganalisis rute yang selamat untuk anak sekolah dengan fasilitas penunjangnya yaitu trayek angkutan umum, jalur pedestrian, jalur pesepeda, dan Zona Selamat Sekolah (ZoSS). Analisis yang digunakan adalah metode Manual Kapasitas Jalan Indonesia, analisis Cross Tab, analisis untuk pejalan kaki, dan analisis deskriptif. Hasil penelitian adalah visi rasio pada ruas-ruas jalan di 5 zona observasi berada di angka 0,13-0,69 dengan tingkat pelayanan jalan di interval A dan F, dengan jumlah pejalan kaki relatif besar serta volume lalu lintas dan kecepatan tinggi. Untuk itu perlu dibangun fasilitas Zona Selamat Sekolah. Dari hasil analisa Cross Tab diketahui bahwa sepeda motor merupakan moda yang paling banyak digunakan diikuti pengguna angkutan umum dan pejalan kaki. Oleh karena itu diperlukan fasilitas pejalan kaki/trotoar dan tempat perhentian angkutan umum guna melindungi semua pengguna jalan. Diperlukan pelikan tunggu dan zebra cross di beberapa ruas jalan karena tingginya volume lalu lintas dan jumlah pejalan kaki yang menyeberang. Persentasi siswa yang menggunakan angkutan umum 19,57%, pengguna sepeda motor 60,15%, pejalan kaki 7,97%, dan pengguna sepeda, bus umum, mobil pribadi 12,31%.